2011
DOI: 10.1007/s11069-011-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential hazard analysis from the viewpoint of flow measurement in large open-channel junctions

Abstract: A robust and reliable risk assessment procedure for hydrological hazards deserves attention. The transport of mixed material in the types of hazard, such as flash floods and debris flows, plays an important role and should be taken into consideration. At present, however, the mixed material transport phenomenon is not systematically and simply included in the procedures for the elaboration of hazard analysis. The consequence is the risk of losing prediction accuracy and of underestimating hazard impacts. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Whereas, for higher confluence angles and discharge ratios, performance of 2D model was compared with experimental results and found that 2D model predictions were better when compared with 1D model. A 3D numerical model was used by Yang and Chen [82] to study separation zone and secondary circulation at confluence. They assumed fully turbulent flow in the 3D model, but the flow is transition from laminar to turbulent in the experimental study.…”
Section: Numerical Studiesmentioning
confidence: 99%
“…Whereas, for higher confluence angles and discharge ratios, performance of 2D model was compared with experimental results and found that 2D model predictions were better when compared with 1D model. A 3D numerical model was used by Yang and Chen [82] to study separation zone and secondary circulation at confluence. They assumed fully turbulent flow in the 3D model, but the flow is transition from laminar to turbulent in the experimental study.…”
Section: Numerical Studiesmentioning
confidence: 99%
“…The ADC measures the velocity of water using a physical principle called the Doppler effect [27,28]. The ADC consists of two transducers that operate independently of each other.…”
Section: Measurements and Data Processingmentioning
confidence: 99%
“…Artificial Neural Network (ANN) is one of branches of the artificial intelligence methodologies which have played important roles in many scientific disciplines for replacing traditional analysis by computer aided ones [5][6][7][8]. MLP and recurrent network are among the most frequently used ANNs for interpretation and recognition of complicated pattern in various fields specially in well testing [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%